2014
DOI: 10.4081/rr.2013.e6
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of neurocognitive and neuropsychiatric manifestations in childhood-onset lupus: an overview

Abstract: This review explores current understanding of neuropsychiatric systemic lupus erythematosus (NPSLE) of childhood onset, in particular neurocognitive impairment. As yet, fewer studies have focused on childhood onset NPSLE compared to adult onset NPSLE and diagnosis still involves the 1999 American College of Rheumatology case definitions of neuropsychiatric syndromes, which were developed for adults. Although a validated core set of neuropsychometric tests exist for childhood onset NPSLE, these still have limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 142 publications
(145 reference statements)
0
2
0
Order By: Relevance
“…Other antibodies with pathogenic relevance to cognitive dysfunction include anti-cardiolipin antibodies (ACL), anti-neuronal antibodies, anti-endothelial-cell antibodies (AECAs) and anti- Nedd5 C-ter antibodies 8-10. Patients with systemic lupus erythematosus (SLE) who have neuropsychiatric involvement were found to have significantly higher levels of matrix metalloproteinase-9 (MMP-9) in their serum and in cerebrospinal fluid (CSF), as compared to those without neuropsychiatric syndromes 11,12…”
Section: Introductionmentioning
confidence: 99%
“…Other antibodies with pathogenic relevance to cognitive dysfunction include anti-cardiolipin antibodies (ACL), anti-neuronal antibodies, anti-endothelial-cell antibodies (AECAs) and anti- Nedd5 C-ter antibodies 8-10. Patients with systemic lupus erythematosus (SLE) who have neuropsychiatric involvement were found to have significantly higher levels of matrix metalloproteinase-9 (MMP-9) in their serum and in cerebrospinal fluid (CSF), as compared to those without neuropsychiatric syndromes 11,12…”
Section: Introductionmentioning
confidence: 99%
“…In particular, genome-wide association studies (GWAS) revealed a strong association of multiple polymorphisms in key genes for interferon-α (IFNα) antiviral-like responses, antigen recognition and presentation, co-stimulation as well as B-and T-cell activation with the development of SLE (7,8). Nonetheless, the hereditary factors involved in the development of specific SLE manifestations have only recently begun to be defined and explored and stand as borderless boroughs of a larger city within the perimeter of general SLE susceptibility (9)(10)(11). Research in this field promises to define the mechanistic bases for prognostic profiling of patients with SLE and for individualised treatment choices.…”
mentioning
confidence: 99%